Comfort for the people and liberation for the housewife: Gender, consumption and refrigerators in Argentina (1930-60) - Pérez, Inés (2012)
The mass consumption of electric refrigerators in Argentina has been linked to several representations. On the one hand, it has occupied a central place in the rhetoric of "welfare democratisation" used by the Peronist government to present a "new Argentina". On the other hand, it took on a prominent role in the search for distinction by the growing middle class, and in the creation of social distance within the middle class. In both cases, the image of the housewife´s "liberation" from daily chores because of new appliances merged with the image of a successful "popularisation of comfort", the social model that fostered this image and the head of the household who could provide a better life for his family. The increase in refrigerator consumption changed the visibility of domestic work in a paradoxical way: as it became a frequent topic in several discursive spaces, it suggested that the housewife´s work had been (or would be) replaced by new appliances. In this article, I examine the meanings ascribed to this appliance through its representation in 45 life narratives and the narratives´ intertextual relationships with texts from the period. This analysis focuses on the ways in which the refrigerator became intertwined with the strategies of distinction used by those who could afford such a product. I also analyse the conditions that allowed the "popularisation" of refrigerators, as well as the discourses that made the product a "must-have".